Finding the best circular distribution for southwesterly monsoon wind direction in Malaysia - Kamisan, N.A.B.; Hussin, A.G.; Zubairi, Y.Z. (Penerbit Universiti Kebangsaan Malaysia, 2010)
In this paper, four types of circular probability distribution were used to evaluate which circular probability distribution gives the best fitting for southwesterly Malaysian wind direction data, namely circular uniform distribution, von Mises distribution, wrapped-normal distribution and wrapped-Cauchy distribution. The four locations chosen were Alor Setar, Langkawi, Melaka and Senai. Two performance indicators or goodness of fit tests which are mean circular distance and chord length were used to test which distribution give the best fitting.